Frequency-dependent polarizabilities and shielding factors for confined one-electron systems. (8th December 2016) - Montgomery, H E; Pupyshev, Vladimir I
Abstract: Frequency-dependent dipole polarizabilities and shielding factors are calculated for the ground state of spherically symmetric screened one-electron systems embedded in an impenetrable spherical cavity. Coulomb, Yukawa, Hulthén and exponential cosine-screened Coulomb potentials are considered. In contrast to free systems, Dirichlet boundary conditions introduce a contribution to the shielding factor that results from an integral over the surface of the confining boundary. This is a fundamental difference between free and confined systems and results in unexpected modifications to some of the classic relations for free systems. The methods derived also give a simple expression for the polarizability of the confined harmonic oscillator as an example of extending the methods of this work to potentials beyond the four studied.